2000
DOI: 10.1002/(sici)1521-4095(200004)12:8<567::aid-adma567>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrins in Polymer Synthesis: Supramolecular Cyclodextrin Complexes of Pyrrole and 3,4-Ethylenedioxythiophene and Their Oxidative Polymerization

Abstract: Dedicated to Professor Helmut Ringsdorf on the occasion of his 70th birthday p-Conjugated polymers, often referred to as conducting polymers or synthetic metals, have created enormous interest over the past 25 years. Due to the substantial p-electron delocalization along their backbones, these polymers show interesting (nonlinear) optical properties and become good electronic conductors when oxidized or reduced. Hence, a prominent and active role is foreseen for these compounds in a variety of practical applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 6 publications
3
60
0
Order By: Relevance
“…weaken this competitive inclusion complexation effect, Meb-CD has come into our sight since it has a higher solubility than b-CD and has been widely used to include a variety of vinyl monomers to enhance their solubility in aqueous media. 31,32 Here Meb-CD was used to include HPMA to depress the dethreading tendency of b-CD off the Pluronic F127 backbone. This strategy was shown to be effective to keep more b-CDs on the polymeric chain while the PRs yields were also improved moderately.…”
Section: Atrp Of Hpma Initiated With Pprs Comprising Brib-f127-ibbr Amentioning
confidence: 99%
“…weaken this competitive inclusion complexation effect, Meb-CD has come into our sight since it has a higher solubility than b-CD and has been widely used to include a variety of vinyl monomers to enhance their solubility in aqueous media. 31,32 Here Meb-CD was used to include HPMA to depress the dethreading tendency of b-CD off the Pluronic F127 backbone. This strategy was shown to be effective to keep more b-CDs on the polymeric chain while the PRs yields were also improved moderately.…”
Section: Atrp Of Hpma Initiated With Pprs Comprising Brib-f127-ibbr Amentioning
confidence: 99%
“…Furthermore, the preparation and polymerization of equimolar cyclodextrin complexes of commercial standard monomers like styrene 1 and methyl methacrylate (MMA have been described. It was also shown that the precipitation polymerization of a cyclodextrin complex of a poorly water-soluble monomer like MMA can be described by kinetic equations similar to those for the classical polymerization in solution [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of -cyclodextrin to encapsulate lipophilic compounds, such as pyrrole, in its hydrophobic activity to form a water-soluble inclusion complex (IC) is well documented [34]. IC formation can significantly lower the vapor pressure of pyrrole.…”
Section: Polypyrrole Incorporation Into Pec Fibersmentioning
confidence: 99%
“…Hence, pyrrole/-cyclodextrin ICs represents a strategy by which pyrrole may be effectively encapsulated within IPC fibers for subsequent polymerization. Additionally, chemical polymerization by FeCl 3 of cyclodextrin encapsulated pyrrole has been reported to precipitate polypyrrole as a powder, with cyclodextrin -hosts‖ retained in solution from which they may be efficiently separated from polypyrrole by sedimentation and washing with water [34].…”
Section: Polypyrrole Incorporation Into Pec Fibersmentioning
confidence: 99%